The role of ethics in data governance of large neuro-ICT projects. (14th May 2018) - Stahl, Bernd Carsten; Rainey, Stephen; Harris, Emma; Fothergill, B Tyr
Abstract: Objective: We describe current practices of ethics-related data governance in large neuro-ICT projects, identify gaps in current practice, and put forward recommendations on how to collaborate ethically in complex regulatory and normative contexts. Methods: We undertake a survey of published principles of data governance of large neuro-ICT projects. This grounds an approach to a normative analysis of current data governance approaches. Results: Several ethical issues are well covered in the data governance policies of neuro-ICT projects, notably data protection and attribution of work. Projects use a set of similar policies to ensure users behave appropriately. However, many ethical issues are not covered at all. Implementation and enforcement of policies remain vague. Conclusions: The data governance policies we investigated indicate that the neuro-ICT research community is currently close-knit and that shared assumptions are reflected in infrastructural aspects. This explains why many ethical issues are not explicitly included in data governance policies at present. With neuro-ICT research growing in scale, scope, and international involvement, these shared assumptions should be made explicit and reflected in data governance.